Microstructure and inertial characteristics of a magnetite ferrofluid over a stretching/shrinking sheet using effective thermal conductivity model - Hussanan, Abid; Mohd Zuki, Salleh; Khan, Ilyas (Elsevier, 2018)
Nanofluid is the most promising gift ofmodern science to improve the heat transfer capabilities of conventional heat transfer fluids.However, one of themost crucial drawbacks for classical nanofluidmodels is that they cannot describe a class of fluids that have certainmicroscopic characters arising fromthe micro-rotation and local structure of the fluid elements. In thiswork, the innovative micropolar nanofluidmodel is introduced to study the microstructure and inertial characteristics of the substructure particles.More exactly, the flow and heat transport of micropolar ferrofluid over a stretching/shrinking sheet subjected to suction and injection is studied. Magnetite- Fe3O4 (iron oxide) nanoparticles are considered in water taken as conventional base fluid. The mathematical model has been formulated based on Tiwari-Das nanofluidmodel. Explicit exact solutions of non-linear coupled momentum equations are obtained. The solution of energy equation is obtained in terms of Whittaker function with the help ofMaple. The impacts of pertinent parameters on velocity,micro-rotation velocity and temperature are shown graphically for positive and negative mass transfer flow and analyzed in detail. The results show that micro-rotation velocity increases first and then decreases. There is a remarkable change occurs to micro-rotation velocity for positive and negative values of mass transfer parameter. Presence of mass transfer parameter accelerate the profiles near the flow domain and then decelerates it. Further,micropolar ferrofluid have higher velocity than the classical nanofluid. Comparison have been made with published data under special cases and obtained in close agreement.